A CHF Model for Pool Boiling on Rough Surface under Exponential Heat Supply - Walunj, Avdhoot; Sathyabhama, Alangar; Mande, Amol; Kolhe, Ravindra; Palande, Dattatray (International Journal of Advanced Engineering Research and Science, 2022)
In present study, the experiments are carried on sample of different surface roughness to investigate the transient heat transfer phenomenon at the saturated condition of the distilled water. The surface roughness (Ra) ranges from 0.106 μm to 4.03 μm. The boiling crisis is observed during each transient heat supply. The high-speed camera of 1000 fps is used to observe the stages of boiling during different transient and to confirm the moment of critical heat flux (CHF). The empirical relation is presented for transient CHF and corresponding heat transfer coefficient (HTC). It is found that transient CHF is a function of both Ra and γ. The hydrodynamic model is developed for prediction of CHF at different rate of exponential heat supply for the wide range of Ra by incorporating γ.